Physical, structural and optical properties of willemite- based glass-ceramic doped with manganese oxide - Mohd Zaid, Mohd Hafiz (2016)
Over the last few decades, great deals of interest have been focused on the fabrication and synthesizing willemite based ceramic. However, only few of them used waste materials to fabricate the willemite in form of glass-ceramic. This research was carried out based on several objectives such as to synthesis and study the effect of ZnO addition on the physical, structure and optical properties of soda lime silica (SLS) glass system. Besides, this work also investigation the effect of various heat treatment temperatures on the physical, structure and optical of precursor glass and glass-ceramics and the influence of MnO doping on the physical, structure and optical properties of willemite based glass-ceramics. Thus, in this study, willemite based glass-ceramics were fabricate and synthesized using SLS glass waste as a source of silicon. A series of precursor glasses in the ZnO-SLS glass system was prepared by the conventional melt-quench technique. Willemite based glass-ceramics were derived from the selected precursor ZnO-SLS glass by a controlled crystallization process. The thermal, chemical and physical properties of precursor glass and glass-ceramics were measured by differential thermal analysis (DTA), energy dispersive X-ray fluorescence (EDXRF), average density and linear shrinkage measurement. The average density and linear shrinkage of glass and glassceramic samples were found increased with increasing of heat treatment temperature and concentration of dopant. Besides, the structural properties of precursor glass and formation of willemite crystal phase, morphology and size with increase in heattreatment temperatures was examined by X-ray diffraction (XRD) and field-emission scanning electron microscopy (FESEM) techniques. The average calculated crystallite size obtained from XRD was found to be in the range 30-60 nm whereas the grain size observed in FESEM was 300-700 nm. Fourier transform infrared (FTIR) reflection spectroscopy was used to evaluate the structural of glass and glassceramics. The appearance of SiO2, ZnO4 and Zn-O-Si bands detected from FTIR measurements indicate that the formation of willemite crystal phase. The study of the optical band gap has found that optical band gap of glass and glass-ceramics decreased as the percentage of dopant and heat treatment temperature increased. The photoluminescence spectra of Mn2+ ions exhibit emission transitions of ⁴T1(G) - ⁶A1(S) and its excitation spectra show an intense absorption band at 260 nm. Prominent green emission colors of α-Zn₂SiO₄ phase were observed centered at 525 nm while the yellow emission centered at 585 nm resulted from β-Zn₂SiO₄ phase. These spectra reveal that the luminescence performance of the glass-ceramics is increase with the progression of dopant percentage and heat treatment temperatures. This enhancement is caused by partitioning of Mn²+ ions into the willemite crystals with progress of heat treatment temperatures. Such luminescent glass-ceramics are expected to find potential applications in phosphors and opto-electronic devices.